Uma estratégia de interação na Web para a análise de sistemas elétricos de potência - Tamashiro, Márcio Augusto (2016)
Currently, many important technical and scientific works are only possible with the aid of computers and specific programs. In Electrical Engineering, these resources are both used in static and dynamic studies of electric power systems, which give support, for example, to the planning, and operation of the grid performed by companies in the sector. Because of this, there is a large number of commercial or non-commercial programs available. Commercial applications are known to be computationally efficient as well as the amount of offered resources; nevertheless, they are not suitable for educational purposes or for conducting research. One of the main reasons pointed out is because they are not open source, and thus they cannot be studied or adapted as needed. Thus, many users, quite often in academia, prefer to create their own applications, most of them written in MATLAB, FORTRAN and C ++ programming languages. These programs are provided as desktop applications usually designed to only one type of study and without user-friendly interface. However, there are a few options with more attractive features such as the existence of a graphical user interface, and number of computational resources close to those found in commercial applications. There are also proposals in the literature for web applications whose main advantage is the remote and simultaneous access by any computer. Generally, the existing applications do not make available real-time collaboration features, and no interoperability with other applications. In this context, this thesis focused on the research of the implementation of a web application for analysis of electrical power systems, exploring these two aspects above mentioned. For that, some similar non-commercial programs and open-source were deeply investigated. In addition, the computational tools necessary to develop the application were selected and presented. The investigations and computational implementation performed here, as well as the results are properly presented and analyzed at the end of this work.